Molecular sieving of linear and branched C6 alkanes by tannin-derived carbons. (15th April 2021) - Castro-Gutiérrez, Jimena; De Oliveira Jardim, Erika; Canevesi, Rafael L.S.; Silvestre-Albero, Joaquin; Kriesten, Martin; Thommes, Matthias; Celzard, Alain; Fierro, Vanessa
Abstract: Two micro-mesoporous carbons (MMCs): a disordered mesoporous carbon (DMC) and an ordered mesoporous carbon (OMC), synthesized by an easy, low-cost, and green method are proposed as efficient hydrocarbon sieves for the separation of C6 isomers: n -hexane (nHEX), 2-methylpenthane (2 MP) and 2, 2-dimethylbutane (22DMB). Their textural characterization reveals a highly interconnected pore network within the DMC, while a reverse hierarchy of ordered mesopores only accessible through narrow micropores is found in the OMC. The pore texture strongly affects their adsorption performance by kinetic and molecular sieving effects; the narrow constrictions in the OMC allow adsorption of nHEX and partially 2 MP but not 22DMB, whereas the highly connected pore network of DMC allows adsorption of the three isomers. Multi-component adsorption isotherms calculated from the single-component experimental results by ideal adsorbed solution theory (IAST) demonstrates that the OMC material has a remarkably high selectivity for the adsorption of nHEX and nHEX + 2 MP from binary and ternary mixtures, respectively. To the best of the authors' knowledge, such behavior has never been reported so far for carbon materials. Hence, this study shows that tannin-derived MMCs have great potential to be used as an eco-friendly and low-cost alternative for the selective separation of di-branched C6 isomers. Graphical abstract: Image 1 Highlights: Mesoporous ordered and disordered carbons, OMC and DMC, were prepared from tannin A reverse hierarchical mesoporous structure is identified in the OMC Branched C6, 2 MP and 22DMB, are partially adsorbed or excluded from the OMC The IAST separation selectivity of nHEX/22DMB is higher than 10 12 OMC outperforms well-known MOFs in nHEX separation selectivity